Manhaju Al-Qur’an fi Iqamati Al-Hujjah ‘Ala Al-Musyrikin fi Surah Al-An’am (Dirasah Tahliliyyah Linamadzij Mukhtarah) - Atlerh Thaer Abdul; Nashwan Abdo Khaled (Studia Quranika, 2022)
The Qur'an represents the support of God for the Prophet, with the arguments and proofs that reasoning and divine. This guidance has formed the approach of the Quran in dealing with the benefactor and the violator and base of the argument on the followers and the advocates. The research limits the Qur'an's approach to responding to the non-believer in Surah al-An’am, using the inductive and analytical approach. The study found; Surah al-An’am consists of many narrations of the non-believer against the Prophetic Commandments. Therefore, the Quranic narration in Surah al-An’am is considered an effective method to deliver the truth to the non-believers and able to limit the conflict and controversy between both parties